Facile fabrication of superhydrophobic polyester fabric based on rapid oxidation polymerization of dopamine for oil–water separation. Issue 43 (9th August 2021) - Xie, Ailing; Wang, Boan; Chen, Xinpeng; Wang, Yahui; Wang, Yirong; Zhu, Xiaowei; Xing, Tieling; Chen, Guoqiang
Abstract : Through the special chemical structure of dopamine, superhydrophobic polyester fabric was fabricated by introducing the low surface energy substance hexadecyltrimethoxysilane into the PET fabric and chelating Fe ions to form rough surface. Abstract : Through the special chemical structure of dopamine (DA), superhydrophobic polyester (PET) fabric was fabricated by introducing the low surface energy substance hexadecyltrimethoxysilane (HDS) into the PET fabric and chelating Fe ions with phenolic hydroxyl groups of polydopamine (PDA) to form a rough surface. The water contact angle (WCA) of the prepared PDA/Fe/HDS PET fabric was higher than 160° and the scrolling angle (SA) was lower than 2.09°. The excellent adhesion property of polydopamine (PDA) on the substrate is helpful to improve the stability of superhydrophobic PDA/Fe/HDS PET fabric. The tests results showed that the modified PET fabric maintains excellent mechanical properties. Its superhydrophobic property had good stability and durability in the harsh environment of washing, mechanical friction, UV irradiation, seawater immersion, acid–base and organic reagents erosion. The PDA/Fe/HDS PET fabric also had good self-cleaning and oil–water separation properties. It still had good oil–water separation performance after repeated use for 25 times, and the separation efficiency was more than 95%. The preparation method was facile, the treatment time can be shortened, the cost of the modified substrate was low, and fluorine-free substances were used in the process. This work provides a new way to expand the added value of PET fabrics and develop durable superhydrophobic fabrics in practical application.